PENINGKATAN KEMAMPUAN MENDESKRIPSIKAN PETUNJUK DENAH MELALUI METODE DEMONSTRASI SISWA KELAS IVSDN 006 PAGARAN TAPAH DARUSSALAM - Marsino ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of ability to describe the upper grade IV directive SDN 006 Pagaran Tapah Darussalam. Goals to be achieved in this research is to improve the ability to describe the Upper Grade IV Directive SDN 006 Pagaran Tapah Darussalam through the application of methods demonstrations conducted during one month. This research was conducted in SDN 006 Pagaran Tapah Darussalam. Classes are meticulous researchers are class IV by the number of students as many as 32 people. This classroom action research was started in early August 2016. The form of the research was a class act. The research instrument consists of instruments teacher and student activity sheets and achievement test. Based on the data that has been presented in chapter IV, that this research is to improve the ability of the user to describe the plan through demonstration method of fourth grade students of SDN 006 Pagaran Tapah Darussalam. Based on the results of the study as described in chapter IV, the research objectives have been achieved. Because of the data known to the average ability of students before the implementation of demonstration methods (preliminary data) is only achieved at an average value of 65.9. Then, after the applied method of demonstration (first cycle), obtained an average score of 71.6 or higher categories, and the second cycle 88 or with a high category, but the performance indicators achieved in 96.9% of students or 31 people